Influences of morphine on the spontaneous and evoked excitatory postsynaptic currents in lateral amygdala of rats - Zhang, J.-J; Liu, X.-D; Yu, L.-C (Physiological research, 2016)
Acute morphine exposure induces antinociceptive activity, but the underlying mechanisms in the central nervous system are unclear. Using whole-cell patch clamp recordings, we explore the role of morphine in the modulation of excitatory synaptic transmission in lateral amygdala neurons of rats. The results demonstrate that perfusion of 10 microM of morphine to the lateral amygdala inhibits the discharge frequency significantly. We further find that there are no significant influences of morphine on the amplitude of spontaneous excitatory postsynaptic currents (sEPSCs). Interestingly, morphine shows no marked influence on the evoked excitatory postsynaptic currents (eEPSCs) in the lateral amygdala neurons. These results indicate that acute morphine treatment plays an important role in the modulation on the excitatory synaptic transmission in lateral amygdala neurons of rats.
Keywords: Rats; krysa rodu Rattus; Animals; Excitatory Postsynaptic Potentials; excitační postsynaptické potenciály; Organ Culture Techniques; Rats, Sprague-Dawley; potkani Sprague-Dawley; amygdala; opioidní analgetika; orgánové kultury - kultivační techniky; Analgesics, Opioid; zvířata; Amygdala; Morphine; morfin